Assessment of the Effects of Aerobic Fitness on Cerebrovascular Function in Young Adults Using Multiple Inversion Time Arterial Spin Labeling MRI - Foster, Catherine; Steventon, Jessica J.; Helme, Daniel; Tomassini, Valentina; Wise, Richard G. (Frontiers in Physiology, 2020)
This cross-sectional study investigated the effects of aerobic fitness on cerebrovascular function in the healthy brain. Gray matter cerebral blood flow (CBF) and cerebrovascular reactivity (CVR) were quantified in a sample of young adults within a normal fitness range. Based on existing Transcranial Doppler ultrasound and fMRI evidence, we predicted a positive relationship between fitness and resting gray matter CBF and CVR. Exploratory hypotheses that higher V.O2peak would be associated with higher GM volume and cognitive performance were also investigated. 20 adults underwent a V.O2peak test and a battery of cognitive tests. All subjects also underwent an MRI scan where multiple inversion time (MTI) pulsed arterial spin labeling (PASL) was used to quantify resting CBF and CVR to 5% CO2. Region of interest analysis showed a non-significant inverse correlation between whole-brain gray matter CBF and V.O2peak; r = −0.4, p = 0.08, corrected p (p′) = 0.16 and a significant positive correlation between V.O2peak and whole-brain averaged gray matter CVR; r = 0.62, p = 0.003, p′ = 0.006. Voxel-wise analysis revealed a significant inverse association between V.O2peak and resting CBF in the left and right thalamus, brainstem, right lateral occipital cortex, left intra-calcarine cortex and cerebellum. The results of this study suggest that aerobic fitness is associated with lower baseline CBF and greater CVR in young adults.